(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Youth civic and political participation has been a central concern of research and public policy. This situation has been motivated by growing signs of disaffection among younger generations, at least regarding conventional forms of participation. This paper explores the range of meanings of political participation, which causes debates among researchers due to diversification of the concept. Furthermore, it provides an overview to the new typology of political behavior, which encompasses all typesof political participation, including conventional and unconventional types of political engagement. The author tries to identify and explore factors which facilitate and hinder political participation in Kazakhstan. Such factors as education, awareness level, educational institutions and family in the process of political socialization of youth are found to have significant influence. Many peer-reviewed articles on political participation were reviewed. Articles were sourced through bibliographic data bases and recent issues of journals known to publish in the field of political participation. Key words: civic and political participation, apathy, non-participation, youth.